Strategic Management Analysis in Technology Companies Amidst Technological Disruption - Maulana Sani; Sri Maryanti; Samsidar Samsidar; Ansri Jayanti; Nenden Hendayani (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The purpose of strategic management is to provide long-term direction, improve efficiency and effectiveness of performance, facilitate adaptation to environmental changes, create competitive advantage through innovation, maximize resources, and understand strengths, weaknesses, opportunities, and threats to achieve company goals optimally and sustainably. This ensures the business maintains focus, relevance, and competitiveness in a dynamic marketplace. This presentation aims to explain how to analyze strategic management in technology companies amidst technological disruption. This presentation uses a narrative analysis approach using secondary data to explain strategic management in technology companies amidst technological disruption. The research results show that strategic management in technology companies amidst technological disruption focuses on strategic agility, continuous innovation, and customer orientation for intelligent decision-making through the adoption of the latest technology, building an adaptive culture, and leveraging data to remain relevant and competitive amidst rapid change, involves transforming culture, business processes, and business models, while also addressing challenges such as resistance to change and high investment.